2021
DOI: 10.1002/dta.3028
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and effects on arachidonic acid metabolism of low doses of cannabidiol following oral administration to horses

Abstract: The increasing availability of cannabidiol (CBD) and anecdotal reports of its antiinflammatory effects has garnered it much interest in the equine industry. The objectives of the current study were to (1) describe the pharmacokinetics of oral CBD in exercising thoroughbreds, (2) characterize select behavioral and physiologic effects, and (3) evaluate effects on biomarkers of inflammation using an ex vivo model. This study was conducted in a randomized balanced 3-way crossover design with a two-week washout per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(53 citation statements)
references
References 43 publications
7
46
0
Order By: Relevance
“…This anatomical investigation continues a recent study carried out on the equine DRG, 8 and was designed to improve knowledge of the cellular distribution of cannabinoid and cannabinoid‐related receptors. Taken together, these findings may support further work on the use of phytocannabinoids in equine medicine although, compared with scientific information on the medical benefits of cannabinoids in laboratory rodents and humans, there is still a paucity of information for horses 19 …”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…This anatomical investigation continues a recent study carried out on the equine DRG, 8 and was designed to improve knowledge of the cellular distribution of cannabinoid and cannabinoid‐related receptors. Taken together, these findings may support further work on the use of phytocannabinoids in equine medicine although, compared with scientific information on the medical benefits of cannabinoids in laboratory rodents and humans, there is still a paucity of information for horses 19 …”
Section: Discussionmentioning
confidence: 74%
“…Taken together, these findings may support further work on the use of phytocannabinoids in equine medicine although, compared with scientific information on the medical benefits of cannabinoids in laboratory rodents and humans, there is still a paucity of information for horses. 19 A growing body of evidence has indicated that cannabinoid and cannabinoid-related receptors play a critical role in nociception by means of central and peripheral mechanisms. 1,4,[20][21][22] Considering that mammals share the same anatomical and electrophysiological aspects of nociceptors, 23 and that the ECS possesses the same benefits regardless of the human or animal species studied, 24 the presence of nine cannabinoid receptors in the equine DRG suggested that cannabinoids might also play a role in pain transmission in equines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All plasma samples were analyzed using liquid chromatography-tandem mass spectrometry (LC-MS/MS) for determination of the concentrations of CBD and its metabolites, 7-hydroxy cannabidiol (7-COH CBD) and 7-carboxy cannabidiol (7-COOH CBD), as previously described. 13…”
Section: Cbd and Metabolite Concentration Determination In Equine Plasmamentioning
confidence: 99%
“…Based on these data, although the therapeutic concentration of CBD is unknown, guinea pigs likely need higher doses and increased frequency of dosing of oral CBD to reach adequate plasma concentrations for therapeutic efficacy. Additionally, it should be noted that horses have shown similarly poor absorption rates of CBD to guinea pigs (Ryan et al, 2021), suggesting hindgut-fermenting species may require unique dosing considerations for oral cannabinoid administration.…”
Section: Discussionmentioning
confidence: 99%